2010
DOI: 10.1016/j.neuron.2010.01.021
|View full text |Cite
|
Sign up to set email alerts
|

The Endocannabinoid 2-Arachidonoylglycerol Produced by Diacylglycerol Lipase α Mediates Retrograde Suppression of Synaptic Transmission

Abstract: Endocannabinoids are released from postsynaptic neurons and cause retrograde suppression of synaptic transmission. Anandamide and 2-arachidonoylglycerol (2-AG) are regarded as two major endocannabinoids. To determine to what extent 2-AG contributes to retrograde signaling, we generated and analyzed mutant mice lacking either of the two 2-AG synthesizing enzymes diacylglycerol lipase alpha (DGLalpha) and beta (DGLbeta). We found that endocannabinoid-mediated retrograde synaptic suppression was totally absent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
503
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 426 publications
(549 citation statements)
references
References 49 publications
42
503
2
2
Order By: Relevance
“…DSE and DSI are not observed in DAGLa-knockout mice, indicating that 2-AG mediates these mechanisms of synaptic plasticity [18,19]. DAGLa is concentrated postsynaptically in dendritic spines that are apposed to CB 1 -expressing axon terminals [62], which is consistent with the notion that 2-AG is synthesized postsynaptically but acts presynaptically.…”
Section: Introduction To Endocannabinoid Signallingsupporting
confidence: 80%
See 1 more Smart Citation
“…DSE and DSI are not observed in DAGLa-knockout mice, indicating that 2-AG mediates these mechanisms of synaptic plasticity [18,19]. DAGLa is concentrated postsynaptically in dendritic spines that are apposed to CB 1 -expressing axon terminals [62], which is consistent with the notion that 2-AG is synthesized postsynaptically but acts presynaptically.…”
Section: Introduction To Endocannabinoid Signallingsupporting
confidence: 80%
“…A second DAGL that is related to DAGLa based on sequence similarity has been identified and is known as DAGLb [17]. However, while DAGLb can catalyse the formation of 2-AG in vitro [17], comparative analysis of the brain content of 2-AG in DAGLa-and DAGLbknockout mice indicates that the contribution of DAGLb to 2-AG biosynthesis in adult brain is much less significant compared with DAGLa [18,19]. 2-AG is inactivated by the enzyme monoacylglycerol lipase (MAGL), which cleaves 2-AG into arachidonic acid and glycerol [20][21][22].…”
Section: Introduction To Endocannabinoid Signallingmentioning
confidence: 99%
“…2-Arachidonoylglycerol (2-AG) and Narachidonoylethanolamine (AEA), 2 arachidonic acid derivatives, are the chief endocannabinoids in the brain; cerebellum CB 1 R are predominantly activated by 2-AG. An increase in the concentration of postsynaptic Ca 2+ either by entry via voltagegated Ca 2+ channels or activation of type 1 metabotropic glutamate receptors brings about the release of 2-AG synthesized from diacylglycerol, a reaction catalyzed by diacylglycerol lipase-alpha in Purkinje cells, with the overall effect of activation of presynaptic CB 1 R [52][53][54][55][56]. In addition, several studies have reported the high density of CB 1 Rs in striatum and the presence of AEA throughout the basal ganglia, in particular in the globus pallidus and substantia nigra [31,57,58].…”
Section: Cannabinoid Receptors and Signaling In Relations To Central mentioning
confidence: 99%
“…The CB 1 receptor is responsible for both DSI/DSE which can be induced by application of CB 1 receptor agonists and are blocked by CB 1 receptor antagonists (Ohno-Shosaku et al, 2002b;Wilson and Nicoll, 2001). Also, both DSI and DSE are mediated by 2-arachidonoylglycerol (2-AG), one of the main eCBs in hippocampus (Gao et al, 2010;Tanimura et al, 2010). While DSI and DSE have been shown to exhibit qualitatively similar behaviour, their quantitative characteristics differ.…”
Section: Introductionmentioning
confidence: 99%